FRI0271 Performance of Modified Rodnan Skin Score in Early Diffuse Cutaneous Scleroderma–Analysis from 4 Cohorts. (15th July 2016) - Khanna, D.; Produman, S.; Frech, T.; Nihtyanova, S.; Domsic, R.; Berrocal, V.; Stevens, W.; Nikpour, M.; Denton, C.; ,
Abstract : Background: The modified Rodnan skin score (mRSS) is used as a primary outcome measure in clinical trials of dcSSc. EUSTAR analysis has proposed that a lower mRSS and earlier disease duration are associated with progressive disease, as defined by worsening mRSS [1]. Objectives: 1. To find an optimal cut off for worsening mRSS in 4 cohorts of dcSSc, and 2. To assess if presence of anti-RNA polymerase III [RNAP] vs. anticentromere /or anti-SCL-70 is associated with different mRSS cut off for worsening disease. Methods: We used 4 cohorts with early dcSSc (defined as ≤60 months from 1st non-RP sign or symptom) – 2 US cohorts [Combined Response Index in Systemic Sclerosis [CRISS] and Prospective Registry in Early Systemic Sclerosis [PRESS]], the UK Royal Free Hospital [RFH] cohort, and the Australian Scleroderma Interest Group [ASIG] cohort. Inclusion criteria included dcSSc diagnosed by a scleroderma physician, mRSS data at 2 time points (12±3 months apart), and availability of disease duration (defined as 1st non Raynaud phenomenon sign or symptom). Worsening of skin fibrosis was defined as increase in mRSS >5 points and ≥25% from baseline to 2nd visit. To identify the optimal cut point of baseline MRSS that yields the highest sensitivity for worsening disease, we developed the ROC curves. For worsening of mRSS, we fitted logistic regression model with worsening as outcome variable and a binary variable of baseline mRSS cut point as predictor. We also explore the differences between the proportion of patients with worsening of mRSS among the patients with presence of RNAP vs. anticentromere /or anti-SCL-70 and tested using proportion z-test. Results: There were 235 patients with early dcSSc included in the analysis. Mean (SD) disease duration was 26.61 (14.67) months, median=23.67 months. We evaluated 3 cut points for disease duration based on inclusion criterion from recent clinical trials: ≤24, 36, and 60 months. For all disease durations, approximately 10.5% of patients had mRSS worsening at 1-year period. A mRSS cut off of 26 had the highest probability of worsening (Table). mRSS of ≤26 was able to enrich worsening mRSS from 10.5% to 15.0% for different cut points but excluded 33–35% of patients with early dcSSc. 64 patients (27.23%) had RNAP and 48 (20.43%) had anti-centromere and anti-SCL-70 and there was no difference in cut off for worsening of mRSS at 1-year. Conclusions: In this preliminary analysis, a mRSS≤26 was the optimal cut point for worsening disease in 4 cohorts with dcSSc. This threshold gained an additional 5% of patients who worsened but excluded 33–35% of patients with early dcSSc. References: Maurer B Ann Rheum Dis 2015 Disclosure of Interest: None declared